Identity Trouble
XIV, 295 p.
Keywords: Identity Trouble assembles contributions from a variety of discourse fields to discuss the pressures on traditional understandings of identity. The focus is on failures and uncertainties in people's construction of their identities when faced change and the contributors raise critical questions about identity and how it may be reconfigured.